Restoration of intestinal continuity after Hartmann's procedure - not a benign operation: are there predictors for morbidity? - Antolovič, Dalibor; Reißfelder, Christoph; Özkan, Timur; Galindo Escobedo, Luis Vidal; Büchler, Markus W.; Koch, Moritz; Weitz, Jürgen (Langenbeck's archives of surgery, 2011)
Background: Restoration of intestinal continuity is usually the second step after Hartmann's procedure and an established procedure in abdominal surgery, particularly for complicated diverticular disease. This descriptive study aimed to examine the morbidity and mortality associated with the procedure and to define potential risk factors. Patients and methods: Data from 161 consecutive patients (median age 62 years, median BMI 25.2) undergoing elective surgery with restoration of bowel continuity between October 2001 and November 2008 at the Department of Surgery, University of Heidelberg, were included in this study. The association of potential prognostic variables with postoperative morbidity and mortality were examined by univariate and multivariate analyses. Results: The median time between the initial operation and the restoration of bowel continuity was 7 months. The median operation time was 185 min with a blood loss of 150 ml and median postoperative hospital stay of 9 days. Fifty-one percent of the patients had an uneventful recovery, whereas 49% had a postoperative complication. Surgical infections occurred in 18% of patients, 3.8% suffered from anastomotic leakage, and surgical re-exploration was necessary in 11.2%. Medical complications occurred in 21.1% of the patients, with pneumonia in 2.5% and urinary tract infections in 1.3%. One patient died 17 days after surgery. Univariate analysis showed that patients taking immunosuppressant drugs had significantly more wound infections and, interestingly, protective ileostomy was associated with postoperative anastomotic stenosis in our cohort. The administration of PRBC and a prolonged hospital were significantly associated with increased postoperative morbidity in the multivariate analysis. Conclusions: Restoration of bowel continuity is a surgical procedure with high overall morbidity. The high morbidity confirmed in our study and various other papers justify a randomized clinical study to investigate the one-stage concept with primary anastomosis against the Hartmann's procedure and its reversal.